THE INFLUENCE OF DIGITAL RHETORIC ON FOLLOWER TRUST IN THE INSTAGRAM ACCOUNT @MALAKAPROJECT.ID - Baskara, Aditya Febrian Surya; Suminar, Panji; Firmansyah, Mas Agus (jfpublisher, 2025)
The rapid expansion of the internet has transformed communication, particularly through social media platforms like Instagram, where digital rhetoric plays a crucial role in shaping follower trust. This study addresses the problem of understanding how different rhetorical elements influence trust among followers of the Instagram account @malakaproject.id, particularly among young adults from Generation Z. The research aims to explore the impact of logical arguments (Logos), emotional appeals (Pathos), and credibility (Ethos) on follower trust. To achieve this, the study employs a mixed-methods approach, utilizing primary data collected through questionnaires and secondary data from relevant literature. The methodology includes validity and reliability testing of the questionnaire items, with data analysis conducted using multiple linear regression, T-tests, and F-tests to assess the relationships between rhetorical elements and follower trust. The findings reveal that the content on @malakaproject.id significantly enhances followers' trust, with logical arguments (Logos) having the most substantial impact, followed by emotional appeals (Pathos) and credibility (Ethos).